SCANNING ELECTRON MICROSCOPIC (SEM) STUDY OF NEMATODE PARASITES OF GOAT IN LUCKNOW DISTRICT UTTAR PRADESH - SAVITA, .; MISHRA, SUMAN; JAISWAL, KAMAL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The goat is a vital milk and meat production source in India and contributes to the national and international economy. Goat production faces multiple challenges; one major problem is parasites leading to high mortality and economic losses. Nematode parasites are major problems to livestock globally, characterized clinically by enteritis, anaemia, emaciation, dehydration, and death. This study revealed the morphological identification of nematode parasites (Haemonchus sp., Oesophagostomum sp., and Trichuris sp.) in goats in the Lucknow region (India). Morphological identification was done by SEM (Scanning Electron Microscope) with the help of Souls in 1982. Scanning electron microscope exposed some species-specific characters, total body length of parasites, posterior region of Haemonchus having well-developed Copulatory Bursa (CB), spicules, Dorsal ray (DR) Anterior region of Haemonchus having cervical papillae (CP), vulval flap, knob, and cervical lamina. Oesophagostomum showed that the collar region on the mouth part and Buccal Capsule (BC) is surrounded by External Corona Radiate (ECR) and Internal Corona Radiate (ICR). Trichuris sp. was showed the anterior end vulva region of the female, and the posterior end of the male was spirally coiled and spicular sheath covered with minute spines (S).